Programming for Corpus Linguistics How to Do Text Analysis with Java - Mason, Oliver (Edinburgh Textbooks in Empirical Linguistics : ETELI, 2022)
The ability to program a computer has become increasingly important in work that involves corpora. Specialised research needs can no longer be met by available software, and purchasing customised programs is usually not an option. This book enables the researcher to write programs for text and corpus processing. Useful techniques are illustrated with the popular programming language Java, which is very well suited for handling textual data, and at the same time easy to learn.Key Featuresa general introduction to programming for readers with a linguistic backgrounda practical introduction to corpus linguistics for readers with a programming background who are new to corpus processinga guide to relevant aspects of Java which will be useful for text processinga variety of sample programs which are in themselves useful tools for corpus research